Exoskeletons - Gagne, Tammy (Engineering the human body., 2020)
Investigates the power of modern exoskeletons to aid and improve the lives of people with mobility issues. Discusses new technology that has made exoskeleton devices more effective, useful, and discreet than ever. Includes a glossary, an index, resources for further information, and text-dependant questions.